Sustainable Tourism as a Source of Income Diversification for Local Communities Through Mediating Effect of Community Empowerment - Yadav, Ritu; Prakash, Chand; Arora, Anshul; Dangi, Amit (Journal of Tourism, Sustainability and Well-being, 2025)
Sustainable tourism is always concerned with fulfilling visitors’ and local communities’ requirements while keeping current and future generations’ interests in mind. Meghalaya, a state of India well known for its natural beauty and rich cultural heritage, offers a wide opportunity for sustainable tourism. This research aimed to develop a framework for establishing the relationship between sustainable tourism and diversifying local communities’ income sources in Meghalaya through the mediating effect of community empowerment. The proposed framework was tested and validated using the PLS-SEM approach in Smart PLS 4.0. A sample of 425 local community members was drawn for the research from the famous tourist places in Meghalaya: Shillong, Cherrapunji, Mawlynnong, and Dawki, based on the multistage cluster sampling technique. Primary data was collected using an enumerator survey. Research findings revealed that sustainable tourism activities significantly enhance income diversification beyond traditional earning sources like agriculture and handicrafts. Also, the research further confirmed the mediating role of community empowerment between sustainable tourism and income diversification. This study recommended strategies for sustainable tourism development and attaining long-term economic and social goals by integrating community empowerment with tourism and income generation in local communities. At the end of the study, future research directions were provided for further research.